The tin forest - Ward, Helen, 1962-; Anderson, Wayne (New York : Dutton Children's Books, 2001)
An old man's persistent dreams transform a garbage dump into a forest full of life.
Keywords: Refuse and refuse disposal -- Fiction; Reclamation of land -- Fiction